KECENDERUNGAN KONVERSI LAHAN DI KAWASAN PENYANGGA KOTA PADANG - M Hagi Akbar; ahyuni .; yudi Antomi (DEPARTEMEN GEOGRAFI FIS UNP, 2017)
This research was purposed to find out: 1) Range of land coverage, 2) Trends of land conversion, and 3) Compatibility between land coverage and RTRW unit. Method used in this research was descriptive quantitative. Data in this research was Landsat TM7 satellite images recorded in 2007 and 2012, and OLI/TIRS8 satellite images recorded in 2017, and data analysis techniques were pans sharpening, supervised classification, overlay, and scoring. Research finding shows that: 1) developed area in 2007, 2012 and 2017, respectively are 642 ha, 1011 ha, and 1472 ha; forest area in 2007, 2012 and 2017, respectively are 2301 ha, 2134 ha, and 2025 ha; mixed-farm area in 2007, 2012 and 2017, respectively are 114 ha, 181 ha, and 277 ha naked land in 2007, 2012 and 2017, respectively are 83 ha, 89 ha, and 95 ha; rice field in 2007, 2012 and 2017, respectively are 2351 ha, 2283 ha, and 1965; bushes in 2007, 2012 and 2017, respectively are 693 ha, 488 ha, and 402 ha. From precision test of images, it was obtained overall accuracy of 86.72%, and kappa coefficient value was 0.8192%. 2) Trend of land conversion from 2007 to 2012 was developed area addition of 495 ha, and trend of land conversion from 2012 to 2017 was developed area addition of 461 ha. 3) Overlay compatibility of land coverage and RTRW unit shows that 73.20% compatible and 26.80% incompatible.